International copyright dimension of internet publications: an overview (2009)
In the past few decades, there has been explosion in the use of the Internet. Many things that are done traditionally are now being taken over by sophisticated gadgets, which allow prompt, easy and efficient delivery of goods and services. Moreover, the Internet also serves as a platform for researches in almost all the fields of human endeavour. It is not surprising therefore that the Internet, given its international status of accessibility, constitutes an international field, which cannot only be studied, or confine to a particular locality. It is based on this nature of the Internet that attempt is being made to give a legal analysis or overview of copyright protection of materials or works uploaded into the Internet. This study is embarked upon to consider the seamless nature of the Internet in the face of national copyright protection granted to works created in each country and which has no extra territorial application.